Activation vs. Experiential Avoidance as a Transdiagnostic Condition of Emotional Distress: An Empirical Study - Fernández-Rodríguez, Concepción; Paz-Caballero, Dolores; González-Fernández, Sonia; Pérez-Álvarez, Marino (Frontiers in Psychology, 2018)
Background: From a contextual transdiagnostic approach, this study focuses on the importance of the processes of Experiential Avoidance and Activation in explaining and treating psychological problems. There exists widespread empirical evidence to suggest that the response pattern known as Experiential Avoidance, a general unwillingness to remain in contact with particular private experiences through the use of maladaptive avoidance strategies, acts as a functional dimension in various psychological problems. Activation, that is, maintaining contact with experiences/conditions of life and consequently with associated sources of reward, is a condition present in most therapeutic processes. Although a great deal of research has analyzed the relationship of the value of reward with the etiology and maintenance of psychological problems, Activation, as a transdiagnostic factor, has been studied less. The aim of this paper is to carry out an empirical study of the relationship between Activation, EA and emotional state and analyze the capacity of these two conditions to discriminate the intensity and symptomatology type in subjects with emotional distress. Methods: The Hospital Anxiety and Depression Scale (HADS), Environmental Reward Observation Scale (EROS) and Behavioral Activation for Depression Scale (BADS) were completed by 240 health center users. Results: Of the participants, 55% showed clinically relevant emotional distress. All cases of depression showed clinical anxiety. To discriminate between subjects without (n = 109) and with emotional distress (n = 131), analyses of the ROC curves and logistic regression analysis identified the BADS-Avoidance/Rumination followed by the EROS. To discriminate between subjects with anxiety but without depression (n = 61) and with anxiety and depression (n = 70), the most efficient scales were EROS followed by BADS-Social Impairment. Conclusion: It was shown that people with no emotional complaints maintained greater contact with life experiences and with environmental sources of reward than those with emotional distress. Response patterns showing Experiential Avoidance and a reduction in Activation responses were associated with clinical distress. A reduction in Activation was the condition which distinguished those people with the greatest distress and also the greatest comorbidity of symptoms of depression and anxiety. These data support the transdiagnostic nature of Activation and suggest greater attention should be paid to this concept.